2020
DOI: 10.1101/2020.11.24.396887
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Npas4aexpression in the teleost forebrain is associated with stress coping style differences in fear learning

Abstract: Learning to anticipate potentially dangerous contexts is an adaptive behavioral response to coping with stressors. An animal’s stress coping style (e.g. proactive-reactive axis) is known to influence how it encodes salient events. However, the neural and molecular mechanisms underlying these stress coping style differences in learning are unknown. Further, while a number of neuroplasticity-related genes have been associated with alternative stress coping styles, it is unclear if these genes may bias the develo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…Another study found upregulation of genes related to learning and memory, synaptic plasticity, and neurogenesis in the hippocampus of poison frogs, which may be related to their increased spatial cognitive abilities (Liu et al 2020). In zebrafish, differences in fear learning between fish with different stress coping styles are associated with differences in the expression of the plasticity related gene npas4a in the basolateral amygdala, hippocampus, and bed nucleus of the stria terminalis (Baker and Wong 2020). These studies demonstrate the detail with which we are beginning to understand the proximate neural mechanisms of cognition in a comparative context.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found upregulation of genes related to learning and memory, synaptic plasticity, and neurogenesis in the hippocampus of poison frogs, which may be related to their increased spatial cognitive abilities (Liu et al 2020). In zebrafish, differences in fear learning between fish with different stress coping styles are associated with differences in the expression of the plasticity related gene npas4a in the basolateral amygdala, hippocampus, and bed nucleus of the stria terminalis (Baker and Wong 2020). These studies demonstrate the detail with which we are beginning to understand the proximate neural mechanisms of cognition in a comparative context.…”
Section: Introductionmentioning
confidence: 99%